Homozygous mutation in PRUNE1 in an Oji‐Cree male with a complex neurological phenotype. Issue 3 (March 2017) - Costain, Gregory; Shugar, Andrea; Krishnan, Pradeep; Mahmutoglu, Saadet; Laughlin, Suzanne; Kannu, Peter
Abstract : The PRUNE1 gene encodes a member of the phosphoesterases (DHH) protein superfamily that is highly expressed in the human fetal brain and involved in the regulation of cell migration. Homozygous or compound heterozygous PRUNE1 mutations were recently identified in five individuals with brain malformations from four families. We present a case of a 2‐year‐old male with a complex neurological phenotype and abnormalities on brain MRI. Re‐annotation of clinical whole‐exome sequencing data revealed a homozygous likely pathogenic variant in PRUNE1 (c.521‐2A>G). These results further delineate a new PRUNE1 ‐related syndrome, and highlight the importance of periodic data re‐annotation in individuals who remain without a diagnosis after undergoing genome‐wide testing. © 2017 Wiley Periodicals, Inc.